1991
DOI: 10.1128/jb.173.1.334-344.1991
|View full text |Cite
|
Sign up to set email alerts
|

Cloning and nucleotide sequence of the firA gene and the firA200(Ts) allele from Escherichia coli

Abstract: The Escherichia coli genefirA, previously reported to code for a small, histonelike DNA-binding protein, has been cloned and found to reside immediately downstream from skp, a gene previously identified as the firA locus. firA encodes a 36-kDa protein. The mutantfirA200(Ts) allele was also cloned and shown to contain three mutations, each mutation giving rise to a single amino acid change. Partially purified wild-type FirA It is well documented that selection for rifampin resistance in Escherichia coli gives… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
38
0

Year Published

1991
1991
2003
2003

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 39 publications
(40 citation statements)
references
References 30 publications
2
38
0
Order By: Relevance
“…This protein has a very conservative structure among the members of the family Enterobacteriaceae (15,18,20,22,43,46), carries a signal sequence that is characteristic of secreted proteins in its precursor form (18,20,21,43), can be found in isolated OM (18,22), and has an unknown function. Only three nucleotides separate the hlpA stop and firA initiation codons (5,16). We have previously shown by using minicells and by complementation assays that the firA gene of S. typhimurium is expressed in the absence of the hipA promoter, i.e., in a plasmid which lacks the 5' terminus of hlpA and where the vector-derived lac promoter is opposite in orientation to firA (17).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This protein has a very conservative structure among the members of the family Enterobacteriaceae (15,18,20,22,43,46), carries a signal sequence that is characteristic of secreted proteins in its precursor form (18,20,21,43), can be found in isolated OM (18,22), and has an unknown function. Only three nucleotides separate the hlpA stop and firA initiation codons (5,16). We have previously shown by using minicells and by complementation assays that the firA gene of S. typhimurium is expressed in the absence of the hipA promoter, i.e., in a plasmid which lacks the 5' terminus of hlpA and where the vector-derived lac promoter is opposite in orientation to firA (17).…”
Section: Discussionmentioning
confidence: 99%
“…The study on the ssc-1 mutation led us to discover and sequence a novel gene of S. typhimurium, the ssc gene (16). The sequence of its analog in E. coli, the firA gene, is also known (5). On the other hand, the gene mutated in the omsA mutant was not identified by Tsuruoka et al (39), but their preliminary evidence suggested that the omsA mutation maps at approximately 4 min on the E. coli chromosome.…”
mentioning
confidence: 99%
“…The skp gene maps at the 4-min region on the chromosome and is located only four bases upstream of genes that encode proteins involved in lipid A biosynthesis [54][55][56], which is an essential component of LPS. Since LPS is also a major component of the outer membrane of E. coli, several studies have addressed its role in the folding of OMPs.…”
Section: Role Of Lipopolysaccharidementioning
confidence: 99%
“…We found that all these proteins possess a 41 amino acid-long highly conserved region. An earlier report mentioned that the E. coli analogue, FirA, has homology with LacA and CysE (as well as to LpxA), but provided no data [6]. LacA, CysE and NodL have previously been shown to be remarkably homologous with each other and to display a common I-G-A-G-S-[L.I,V,M]-V motif, named as the 'the acetyltransferase motif.…”
Section: Discussionmentioning
confidence: 99%
“…The Sahnonella typhimuriurn mutant SH7622, which carries the mutant allele sscl, is extremely sensitive to numerous hydrophobic antibiotics at growth-permissive temperatures and does not grow at 42°C [4,5]. S. typhimurium ssc and its Escherichia cell analogue firA are highly homologous (identity, 88%) as are the corresponding proteins Ssc and FirA (identity, 96%) [4,6]. We are currently trying to identify the function of Ssc.…”
Section: Introductionmentioning
confidence: 99%